2016
DOI: 10.1186/s12913-016-1578-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection among patients with diabetes mellitus in Dammam, Saudi Arabia

Abstract: BackgroundData regarding comorbidities of hepatitis C virus infection (HCV) in the kingdom of Saudi Arabia (KSA) are lacking. The present study aimed to determine the prevalence and risk factors of HCV among Saudi patients with diabetes mellitus (DM) in Dammam, KSA.MethodsIn this cross-sectional study done in 2011, a total of 1054 Saudi DM patients were randomly selected from the Diabetes Center in Dammam Medical Complex, KSA, for interview and HCV screening using the HCV Rapid Test. Positive cases were later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 14 publications
(36 reference statements)
6
23
3
7
Order By: Relevance
“…Due to multiple factors, such as suppression of immune defense, microangiopathy, and the hyperglycemic environment, patients with DM are more vulnerable to infection and tend to experience increased mortality from infectious diseases (Korbel et al, 2018;Zoppini et al, 2018). It has been suggested that hepatitis B/C virus and tuberculosis infections are more prevalent in diabetic patients (Ba-Essa et al, 2016;Ronacher et al, 2015;Zhu et al, 2016). Furthermore, increasing reports indicate that there is an association between type 2 diabetes mellitus (DM-2) and KSHV infection or the development of KS (Caselli et al, 2014;Ingianni et al, 2007;Sobngwi et al, 2008), while the evidence is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Due to multiple factors, such as suppression of immune defense, microangiopathy, and the hyperglycemic environment, patients with DM are more vulnerable to infection and tend to experience increased mortality from infectious diseases (Korbel et al, 2018;Zoppini et al, 2018). It has been suggested that hepatitis B/C virus and tuberculosis infections are more prevalent in diabetic patients (Ba-Essa et al, 2016;Ronacher et al, 2015;Zhu et al, 2016). Furthermore, increasing reports indicate that there is an association between type 2 diabetes mellitus (DM-2) and KSHV infection or the development of KS (Caselli et al, 2014;Ingianni et al, 2007;Sobngwi et al, 2008), while the evidence is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes and hepatitis C infection are major public health problems worldwide [1] [2]. It is estimated that there are approximately 387 million cases of diabetes in the world.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there are approximately 387 million cases of diabetes in the world. This number can reach 592 million by 2035 and 185 million the number of patients with viral hepatitis C, 80% of whom are chronic carriers [1] [3] [4]. It is a major cause of morbidity and mortality because it can be complicated by cirrhosis and hepatocellular carcinoma [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ao longo dos anos, a literatura internacional tem apontado surtos de infecção pelo vírus da hepatite B (HBV) e vírus da hepatite C (HCV) em instituições hospitalares, ambulatoriais e de longa permanência. Os casos de infecção têm-se mostrado mais frequentes em pacientes com diabetes mellitus (DM) do que naqueles sem a doença, sugerindo que os pacientes com DM sejam potencialmente mais susceptíveis à infecção pelo HBV e HCV em decorrência dos procedimentos relacionados ao tratamento e controle da doença, em especial o monitoramento da glicemia capilar (THOMPSON et al, 2009;BENDER et al, 2012;LANINI et al, 2012;REILLY et al, 2012;SCHAFFZIN et al, 2012;SCHILLIE et al, 2012;DIERCKE et al, 2015;BA-ESSA;MOBARAK;AL-DAGHRI, 2016;INAYAT;RAI, 2016;KANWAL et al, 2016). Reconhece-se que quando as normas de controle de infecção durante o monitoramento da glicemia capilar são negligenciadas, tais como, o compartilhamento de canetas lancetadoras, lancetas e de glicosímetros sem o devido processo de desinfecção, pode ocorrer transmissão de microrganismos pelo sangue (KLONOFF;PERZ, 2010;THOMPSON et al, 2010).…”
Section: Introdução I N T R O D U ç ã O | 15unclassified
“…Estudos sobre a prevalência de infecção pelo HCV em pacientes com e sem DM mostram que pacientes com DM apresentam maior prevalência de infecção pelo HCV (CADRANEL et al, 2008;NWOKEDIUKO;OLI, 2008;BA-ESSA;MOBARAK;AL-DAGHRI, 2016;KANWAL et al, 2016).…”
Section: Introdução I N T R O D U ç ã O | 15unclassified